Stream water quality variation as a function of physical environmental conditions in an agriculturally dominated catchment - Zsigmond Tibor; Farkas Csilla; Bódi Andor; Bakacsi Zsófia; Tóth Eszter; Dencső Márton; Horel Ágota (Journal of Hydrology and Hydromechanics)
The aim of the present study was to investigate stream turbidity and water chemical parameters under varying environmental conditions. We analyzed a three-year-long (2021-2023) daily and bi-weekly dataset collected at six points (P1-P6) along a small stream. We measured stream water turbidity (FNU), total dissolved inorganic nitrogen (TDIN) content, water pH, and specific conductivity (SPC). Meteorological data were collected at the catchment outlet. Daily data showed a moderate positive correlation between FNU and precipitation (r=0.42, p<0.001), while weak negative connections were observed between SPC and FNU values (r=-0.14, p=0.011, n=349). The FNU values at the groundwater spring-fed sampling point (P3) were significantly different from the other sampling points on most parameters (p<0.05). The results of the cluster analysis revealed three main clusters based on daily turbidity data. These groups of daily precipitation totals were i) below 4.8 mm, ii) averaging 6.3 mm, and iii) averaging 23.7 mm. The clusters were most significantly separated along precipitation and FNU values. Turbidity values were strongly correlated with precipitation events for two days, after which stream water quality returned to baseline. Stream water quality was not significantly influenced by soil management or antecedent moisture content but rather by water origin (i.e., precipitation, groundwater).